2013
DOI: 10.1371/journal.pone.0078464
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells (MSC) Prevented the Progression of Renovascular Hypertension, Improved Renal Function and Architecture

Abstract: Renovascular hypertension induced by 2 Kidney-1 Clip (2K-1C) is a renin-angiotensin-system (RAS)-dependent model, leading to renal vascular rarefaction and renal failure. RAS inhibitors are not able to reduce arterial pressure (AP) and/or preserve the renal function, and thus, alternative therapies are needed. Three weeks after left renal artery occlusion, fluorescently tagged mesenchymal stem cells (MSC) (2×105 cells/animal) were injected weekly into the tail vein in 2K-1C hypertensive rats. Flow cytometry sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 27 publications
10
48
0
1
Order By: Relevance
“…Interestingly, in consistent with the findings in the present study, a most recent study showed that IV-injected MSCs localized into the kidneys and blocked the increase of pro-inflammatory factors IL-1β and TNF-α in the renal medulla [35], which was accompanied with normalization of the increased expression of pro-hypertensive renin-angiotensin system and the reduced expression of anti-hypertensive gene (type 2 angiotensin II receptor) in the renal medulla in two kidney-one clip rat, a renovascular hypertension model. Therefore, it is possible that there may also be interaction and regulation of pro-/anti-hypertensive genes by stem cells in the kidneys of Dahl S rats, a salt sensitive hypertension model, which is worth further evaluation.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in consistent with the findings in the present study, a most recent study showed that IV-injected MSCs localized into the kidneys and blocked the increase of pro-inflammatory factors IL-1β and TNF-α in the renal medulla [35], which was accompanied with normalization of the increased expression of pro-hypertensive renin-angiotensin system and the reduced expression of anti-hypertensive gene (type 2 angiotensin II receptor) in the renal medulla in two kidney-one clip rat, a renovascular hypertension model. Therefore, it is possible that there may also be interaction and regulation of pro-/anti-hypertensive genes by stem cells in the kidneys of Dahl S rats, a salt sensitive hypertension model, which is worth further evaluation.…”
Section: Discussionsupporting
confidence: 92%
“…MSCs reduce renin, angiotensin-converting enzyme (ACE), and angiotensin II type 1 (AT1) receptor expression, and lead to reductions in BP, inflammation, and fibrosis [46, 47]. The MSC inhibitory effect on RAS is more stable than ACE inhibitors [47].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reported studies representing a wide spectrum of diseases reinforce this expectation. For example, MSC transplant has proven to be beneficial in preclinical as well as clinical studies of heart disease[92-105], renal disease[106-142], lung disease[143-159], liver disease[160-175], neural system disease[176-204], bone damage[205-227], skin wound healing[228-244], autoimmune disease[245-265], infectious diseases and sepsis[266-287], allergies and asthma[288-306], graft vs host disease[307-325] and diabetes[326]. …”
Section: Prospective Therapeutic Use Of Msc Transplantmentioning
confidence: 99%